Economic Losses and Mitigation after an Employment Termination Theory, Applications, and Case Studies - Steward, Dwight (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This Palgrave Pivot provides a conceptual and practical discussion of the factors that comprise a standard economic damage model in an employment termination case. This book discusses the economic factors and assumptions that comprise an economic damages model in an employment termination case. It also provides a discussion of the valuation of employee fringe benefits and employee stock option valuations. Background on the concept of discounting and discussions of the required information in employment cases are also provided. Readers are able to see the analysis in action, with case studies revolving around highly skilled individuals, less skilled individuals, public sector employees, highly educated individuals, managers and executives, and defamation and damage to reputation.
1. Employment Economic Damage Models Overview -- 2. Plaintiff's Job Search Activities Post-Employment Termination -- 3. Labor Market Analysis and Mitigation following Termination -- 4. Valuation Concepts for Back and Front Pay Losses -- 5. Labor Market and Job Search Research Review -- 6. Valuation of Stock Based Employee Compensation -- 7. Document Requests for Back and Front Pay Analyses -- 8. Case Study Set 1: Highly Skilled Individuals -- 9. Case Study Set 2: Less Skilled Individuals -- 10. Case Study Set 3: Public Sector Employees -- 11. Case Study Set 4: Highly Educated Individuals -- 12. Case Study Set 5: Managers and Executives -- 13. Case Study Set 6: Defamation and Damage to Reputation -- 14. Labor Market Data Sources.
Keywords: Law and economics; Labor economics; Population-Economic aspects; Civil law; Law and Economics; Labor and Population Economics; Civil Law